The Development of Android-Based TMC (Thermochemical) Learning Media Assisted by Smart Apps Creator to Improve Students’ Learning Outcomes - Mellyta Uliyandari; Sutarno Sutarno (Universitas Muhammadiyah Sidoarjo, 2023)
One form of technological development in field of education is the creation of various Android-based learning media. The purpose of this study was to develop Android-based Thermochemical (TMC) learning media assisted by Smart Apps Creator to improve student s’ learning outcomes in thermochemical material. The development in this study was carried out with a 4-D design, define, design, develop, and disseminate. The results of the study show that TMC learning media is very feasible to use based on the validation results two validators,namely material experts and media experts. The learning media validation score by material experts was 75 in